2021
DOI: 10.1038/s41598-020-79785-y
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CR6-interacting factor 1 suppresses keloid fibroblast growth via the TGF-β/Smad signaling pathway

Abstract: Keloids are a type of aberrant skin scarring characterized by excessive accumulation of collagen and extracellular matrix (ECM), arising from uncontrolled wound healing responses. While typically non-pathogenic, keloids are occasionally regarded as a form of benign tumor. CR6-interacting factor 1 (CRIF1) is a well-known CR6/GADD45-interacting protein, that has both nuclear and mitochondrial functions, and also exerts regulatory effects on cell growth and apoptosis. In this study, cell proliferation, cell migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In our study, keloid fibroblasts separated from keloids showed aberrantly higher proliferation, motility, ECM synthesis compared to normal fibroblasts which was consistent with keloids clinical characteristics. Previous reports have also suggested that KFs showed reduced apoptosis, increased proliferation and collagen producing 20,21 …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In our study, keloid fibroblasts separated from keloids showed aberrantly higher proliferation, motility, ECM synthesis compared to normal fibroblasts which was consistent with keloids clinical characteristics. Previous reports have also suggested that KFs showed reduced apoptosis, increased proliferation and collagen producing 20,21 …”
Section: Discussionmentioning
confidence: 86%
“…Previous reports have also suggested that KFs showed reduced apoptosis, increased proliferation and collagen producing. 20,21 We found PTP1B acted as a negative regulator in keloid fibroblasts. It inhibited KFs biological behaviours such as proliferation and motility which play important roles in the genesis, maintenance and progression of keloids, and synthesis of ECM, including collagen I, a major constituent of the dermis, is likely responsible for the bulk of this increased tissue mass, α-SMA which was tightly linked with increased skin tension and constant stretching in keloid and characterizes myofibroblasts differentiation and affects cell contraction and matrix remodelling in turn, MMP2 which is reported to be upregulated in keloids and participates in matrix degradation and cell invasion.…”
Section: Erk Inhibitor Fr180204 Reverses the Effects On Cell Prolifer...mentioning
confidence: 80%
“…21 Inhibition of CRIF1 reduces the production of collagen, and suppresses the abilities of cell proliferation and migration of keloid fibroblasts, and thus inhibits the overgrowth of keloid fibroblasts via inhibiting TGF-β/Smad signalling pathway. 22 ATF3 induces the activation of TGF-β/Smad signalling pathway in keloid fibroblasts to accelerate growth and invasion, and suppress apoptosis of keloid fibroblasts. 23 Thus, these findings show that the TGFβ/Smad signalling pathway plays a crucial role in the formation of keloids.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts, the primary effector cells in keloids, eventually lead to keloid formation by inducing a persistent inflammatory response and excessive ECM deposition ( Suarez et al, 2015 ; Luo et al, 2017 ). This process is driven by many growth factors, including transforming growth factor -β (TGF-β), platelet-derived growth factor (PDGF), fibroblast growth factor β (FGF-β), and insulin-like growth factor I (IGF-I) ( Andrews et al, 2016 ; Nagar et al, 2021 ). In keloids, the effects of these growth factors on fibroblasts contribute to the enhanced scar phenotype.…”
Section: Keloid Pathogenesis Studymentioning
confidence: 99%